Teknologi Pembuatan Pupuk Kompos Dari Limbah Biohidrogen Buah Maja (Aegle marmelos (L) correa) Dengan Menggunakan Starter Kotoran Kambing - Ramli, Irawati; wahab, Nurhikmah (Department of Electrical Engineering, University of Patria Artha, 2022)
Hydrogen is an alternative energy source that can be produced from renewable energy sources, such as biomass and is known as biohydrogen. In addition to abundant producing sources, biohydrogen is also environmentally friendly. But this biohydrogen industry will produce waste that will pollute the environment if simply thrown away. Industrial liquid waste can have a considerable impact on the environment, this waste can cause biological oxygen demand (BOD) and chemical oxygen demand (COD). The high value of BOD and COD produced by this waste resulted in it not being discharged directly into the environment and special treatment was needed in advance. Technology that can be used in handling waste problems, among others, is the utilization of microorganisms as an effort to speed up the process of decomposition of waste, especially organic waste into organic fertilizers. Biohydrogen waste contained in the biohydrogen fermenter tank, then filtered biohydrogen waste which was originally in the form of slury, liquid waste is discharged and solid waste is stored to be mixed with goat manure. A mixture of biohydrogen waste and goat manure is made with a ratio of 20: 80 ; 40:60 ; 60:40 and 80:20 after all the ingredients are well mixed then the sample is stored in a sealed container that has previously been fitted with a thermometer to measure the temperature of the compost. The compost mixture sample is then stored for 30 days and observed its temperature and pH every day, and measured the moisture content at the beginning of the composting process and the end of composting After 30 days of storage the compost mixture is then analyzed nitrogen (N), phosphorus (P), potassium (K) levels. In the research on making compost from biohydrogen waste with maja fruit raw materials obtained the best results, namely at a ratio of 60:40 with N levels of 0.05%, P levels of 0.15% and K levels of 0.61%.